Diseases of Cannabis sativa Caused by Diverse Fusarium Species - Gwinn, Kimberly D.; Hansen, Zachariah; Kelly, Heather; Ownley, Bonnie H. (Frontiers in Agronomy, 2022)
The economic importance of products derived from Cannabis sativa and the potential of species of Fusarium to cause significant economic losses due to plant productivity and mycotoxin residues are the subjects of this review. Sixteen species of Fusarium, reported as associated with cannabis production, are classified in six species complexes: Fusarium oxysporum, F. solani, F. incarnatum-equiseti, F. sambucinum, F. tricinctum, and F. fujikuroi. Taxonomy in this genus is the subject of debate, and removal of species in the F. solani Species Complex to the genus, Neocosmospora, has been proposed. Many species associated with C. sativa are also opportunistic pathogens of humans and animals. Species of Fusarium produce a myriad of mycotoxins, including at least three (deoxynivalenol, zearalenone, and fumonisin B) deemed the most important mycotoxins in human and animal foods. These chemicals vary from the very simple chemicals (butanolide and butanolide) to the structurally complex depsipeptides (beauvericin and enniatin B) and trichothecenes (deoxynivalenol and its acetylated derivatives, diacetoxyscirpenol, and T-2-toxin). Robust strategies for disease management include exclusion of the pathogen, control of environment, and host resistance, but these are in development for this new crop. Biopesticides have been labelled for use on C. sativa; however, few efficacy trials have been performed. Host resistance to these pathogens and transmission are also understudied. The new markets for C. sativa and its derivative products require knowledge for control of these fungal diseases in order to provide safe products for human consumption.